"Into and Out of" the Qinghai‐Tibet Plateau and the Himalayas: Centers of origin and diversification across five clades of Eurasian montane and alpine passerine birds. Issue 17 (4th August 2020) - Päckert, Martin; Favre, Adrien; Schnitzler, Jan; Martens, Jochen; Sun, Yue‐Hua; Tietze, Dieter Thomas; Hailer, Frank; Michalak, Ingo; Strutzenberger, Patrick
Abstract: Encompassing some of the major hotspots of biodiversity on Earth, large mountain systems have long held the attention of evolutionary biologists. The region of the Qinghai‐Tibet Plateau (QTP) is considered a biogeographic source for multiple colonization events into adjacent areas including the northern Palearctic. The faunal exchange between the QTP and adjacent regions could thus represent a one‐way street ("out of" the QTP). However, immigration into the QTP region has so far received only little attention, despite its potential to shape faunal and floral communities of the QTP. In this study, we investigated centers of origin and dispersal routes between the QTP, its forested margins and adjacent regions for five clades of alpine and montane birds of the passerine superfamily Passeroidea. We performed an ancestral area reconstruction using BioGeoBEARS and inferred a time‐calibrated backbone phylogeny for 279 taxa of Passeroidea. The oldest endemic species of the QTP was dated to the early Miocene (ca. 20 Ma). Several additional QTP endemics evolved in the mid to late Miocene (12–7 Ma). The inferred centers of origin and diversification for some of our target clades matched the "out of Tibet hypothesis' or the "out of Himalayas hypothesis" for others they matched the "into Tibet hypothesis." Three radiations included multiple independent Pleistocene colonization events to regions as distant as the Western Palearctic and the Nearctic. We conclude that faunal exchange between the QTP and adjacent regions was bidirectional through time, and the QTP region has thus harbored both centers of diversification and centers of immigration. Abstract : The Qinghai‐Tibet Plateau (QTP) is considered a source region for colonization of adjacent areas such as the northern Palearctic. Using an ancestral area reconstruction approach on a phylogeny of 279 bird species, we suggest that faunal exchange between the QTP and adjacent regions was bidirectional through time and the QTP region has harbored both centers of diversification (for example of snowfinches) and centers of immigration.